Keberhasilan Penerapan SIA sebagai Variabel Pemoderasi atas Hubungan Komitmen Organisasional dan Kinerja - Adli Adli (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2014)
The purposes of this study is to test: (1) the influence of organizational commitment oncompanies financial performance; and (2) the influence organizational commitment andsuccess of implementation accounting information system both jointly on companiesfinancial performance. The study was conducted survey method, consist of 38 BUMNin Indonesia, the sample was taken by using simple random sampling from populations.The collected were used questioners, and the validity and reliability of the data wastested before hypothesis testing. The data analysis for hypothesis testing using moderated regression analysis was processed by SPSS 16 software. The result of this studyshow that: (1) The organizational commitment significance effect on companies financialperformance; and (2) The organizational commitment and success of implementationaccounting information system both jointly significance effect on companies financialperformance specially on ROA dimension.